1999
DOI: 10.1007/bf02738628
|View full text |Cite
|
Sign up to set email alerts
|

Systemic administration of lipopolysaccharide increases plasma leptin levels

Abstract: Lipopolysaccharide (LPS) is known to produce several central and neuroendocrine effects and some of these effects are believed to be mediated through cytokines and other proteins. One such protein, leptin, produced by adipose tissue has been shown to cause anorexia, a central effect associated with LPS treatment. This raised the possibility that LPS-induced effects on feeding behavior may be mediated through leptin. This study was done to investigate the effects of systemic administration of LPS on plasma lept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
25
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 38 publications
4
25
0
1
Order By: Relevance
“…LPS increases leptin (23), which in turn induces POMC activation (20). The CR50% animals in the present study demonstrated an attenuation of leptin expression at 2 h post-LPS.…”
Section: Cr Sickness Behavior and A Potential Mechanismsupporting
confidence: 53%
“…LPS increases leptin (23), which in turn induces POMC activation (20). The CR50% animals in the present study demonstrated an attenuation of leptin expression at 2 h post-LPS.…”
Section: Cr Sickness Behavior and A Potential Mechanismsupporting
confidence: 53%
“…activated cytokine production in the brain and at the periphery including in adipose tissue, liver, and spleen. In another study, LPSinduced leptin release was mediated through IL-1␤ because a soluble IL-1␤ receptor antagonist completely blocked the LPS-induced increase in the leptin levels (Francis et al, 1999). Thus, we can conclude that Hp-LPS-induced protection and adaptation resulting in the limitation of ASA damage may depend upon leptin expression and release and, as shown in this study, could also be mediated by neuropeptides released from sensory afferent nerves.…”
Section: Discussionsupporting
confidence: 68%
“…Its plasma levels are directly correlated with adipose tissue mass and act at hypothalamic central level as a satiety factor inducing a decrease in food intake and an increase in energy consumption [3]. Several studies have demonstrated that acute infection, sepsis, and a wide range of inflammatory mediators increase serum leptin levels, suggesting that leptin is a part of the immune response and host defense mechanisms [4][5][6]. It has been reported that circulating leptin levels are highly and promptly increased in experimental models of acute inflammation [7].…”
Section: Introductionmentioning
confidence: 99%